Happy Birthday, Professor Zhou Yulin (Journal of Partial Differential Equations, 1993)
Some properties of the singular integral operator G(&#8901) and the solvabilityof Cauchy problem for the singular integral-differential equations (1.1) and (1.2) offinite-depth fluids are studied.